2016
DOI: 10.1111/irv.12428
|View full text |Cite
|
Sign up to set email alerts
|

Physician's knowledge, attitudes, and practices regarding seasonal influenza, pandemic influenza, and highly pathogenic avian influenza A (H5N1) virus infections of humans in Indonesia

Abstract: Indonesia has reported highest number of fatal human cases of highly pathogenic avian influenza (HPAI) A (H5N1) virus infection worldwide since 2005. There are limited data available on seasonal and pandemic influenza in Indonesia. During 2012, we conducted a survey of clinicians in two districts in western Java, Indonesia, to assess knowledge, attitudes, and practices (KAP) of clinical diagnosis, testing, and treatment of patients with seasonal influenza, pandemic influenza, or HPAI H5N1 virus infections. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Emerging pathogens. In the last few years a number of emerging viruses have been identified globally, including FLU subtypes (H5N1, H5N6, and H7N9 [106][107][108]) and CoV strains (MERS-CoV [109]\and SARS-CoV [110]). A number of guidelines have been published to help in the diagnosis and management of these emerging pathogens (111)(112)(113).…”
Section: Other Us and International Guidelines Concerning Specific mentioning
confidence: 99%
“…Emerging pathogens. In the last few years a number of emerging viruses have been identified globally, including FLU subtypes (H5N1, H5N6, and H7N9 [106][107][108]) and CoV strains (MERS-CoV [109]\and SARS-CoV [110]). A number of guidelines have been published to help in the diagnosis and management of these emerging pathogens (111)(112)(113).…”
Section: Other Us and International Guidelines Concerning Specific mentioning
confidence: 99%
“…Similarly, when asked about the best measure to prevent swine flu, only 42 (25.3%) students replied it as vaccination (p-value 0.011). These findings of awareness about vaccination should be [12,13] taken seriously as little knowledge about this important aspect of swine flu will badly affect the management of patients during outbreaks. Here lies the responsibility of medical educationists to engage medical & dental students in all types of seminars and awareness campaigns programs for common epidemics like swine flu, Dengue Fever and Congo Fever etc.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the reported vaccination rate for healthcare workers varies between 13.1% and 60%, depending on the country and the influenza season. [11][12][13][14][15] Antón-Ladislao et al [14] reported that the vaccination rate was much higher (71%) in physicians aged ≥45 years and with an increased awareness of the risks of influenza. The rate of vaccination of physicians remains insufficient in our country.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 64% of our study participants specified that the primary reasons for non-vaccination were neglect or a lack of belief in the importance, as has also been reported in other studies. [13,16] Additional research conducted in our country has demonstrated that also among the most common reasons for not receiving a vaccination are lack of time, [8] lack of confidence that the vaccine would provide sufficient protection, [9] and disbelief in the effectiveness of the vaccine. [10] The results of our study revealed that the awareness of physicians who are expected to support vaccination was not sufficient.…”
Section: Discussionmentioning
confidence: 99%